Detection of potential large Maya settlements in the northern Petén area (State of Campeche, Mexico) using optical and radar remote sensing. (February 2019) - LaRocque, Armand; Leblon, Brigitte; Ek, Jerald
Abstract: This study presents preliminary results on the detection of four potential Maya settlements (designed hereafter Sites A, B, C, and D) in the northern Petén area (State of Campeche, Mexico) often referred as the Petén Campechano, using new types of freely available Landsat-8 OLI optical and Sentinel-1A C-band dual-polarized images acquired during the dry and wet seasons. The study also uses the SRTM digital elevation model. Features extracted from the images and DEM over these potential sites were compared to corresponding features from four well-documented Maya cities located in the study area (El Mirador, Calakmul, Uxul, and Yaxnohcah), indicating similar horizontal and vertical dimensions as well as vegetation patterns. The known Maya cities and potential sites are all located adjacent to expansive seasonal wetlands (bajos) following a common locational pattern in Maya urban centers. Further, these sites are also located at intersections of linear features that were interpreted as potential raised causeways (sacbeob) documented in this and other projects. This paper examines both the implications and limitations of these findings, as well as the need for ground verification of these features in future field research. Highlights: SRTM-DEM 3D model produced allows visualizing large raised features hidden by a dense canopy. Topographic SRTM-DEM cross-section highlights the profile of human features and their topographic position. The shadowing effect over Sentinel-1 SAR images confirms the presence of elevated features. Optical Landsat-8 OLI images are able to map the vegetation and to detect structures emerging over the forest. SRTM-DEM, SAR and optic satellite free imagery could be useful to detect potential old Maya settlements hidden by a dense forest cover.